Giant Gyroid and Templates from High-Molecular-Weight Block Copolymer Self-assembly - Park, Sungmin (Sci Rep, 2016)
We present a feasible approach to the direct development of three-dimensionally (3D) bicontinuous gyroid (GYR) nanostructure in high-molecular-weight, composition-controlled polystyrene-b-poly(methyl methacrylate) (PS-b-PMMA) films. The use of a neutral solvent vapor to elaborately control the swelling of block copolymer (BCP) films is essential to generate a direct pathway to GYR (or giant GYR) structure through a hexagonal (HEX) cylindrical morphology in the same material, because the thermal ordering of highly entangled BCP imposes the limit on the chain mobility. Along with the improved mechanical strength arising from the high molecular weight property of the polymers, the structural integrity and overall excellence of a large-scale GYR morphology were confirmed by the results of membrane performance, which showed greater permeability through the nanoporous GYR structure up to by a factor of three than that through the HEX structure. Moreover, a 3D nanoporous GYR template was applied to an affordable material to reproduce an inverse skeletal replica of the GYR structure with its structure being uniformly interconnected. This simple approach to the GYR template, owing to its structural tunability in a controlled composition of BCP, is anticipated to be applicable to a wide range of materialization for practical systems.